Are video‐based preference assessments without access to selected stimuli effective?. Issue 4 (30th August 2015) - Clark, Daniel R.; Donaldson, Jeanne M.; Kahng, SungWoo
Abstract : This study extended the findings of Snyder, Higbee, and Dayton (2012) by presenting items via video during a paired‐stimulus preference assessment but without providing access contingent on selection. Subsequently, items identified as highly, moderately, and less preferred were assessed in a concurrent reinforcer assessment, which suggested that these items did indeed function as reinforcers.